Avaliação de usabilidade em aplicativos interativos para a TVDigital Terrestre - Costa, João; Lemos, Alexandre; Stein, Mônica (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2010)
This paper describes a Digital TV usability research that aims to explore different navigation paradigms in interactive TV applications using the remote control and their acceptance by average spectators.